Gaps in Hospice and Palliative Care Research: A Scoping Review of the North American Literature - Rebecca Antonacci; Carol Barrie; Sharon Baxter; Sarah Chaffey; Srini Chary; Pamela Grassau; Chad Hammond; Mehrnoush Mirhosseini; Raza M. Mirza; Kate Murzin; Christopher A. Klinger (Journal of Aging Research)
Background. The demand for hospice and palliative care is growing as a result of the increase of an aging population, which is most prominent in North America. Despite the importance of the topic and an increase in hospice and palliative care utilization, there still are gaps in research and evidence within the field. Aim. To determine what gaps currently exist in hospice and palliative/end-of-life care research within the context of a North American setting to ensure that future directions are grounded in appropriate evidence. Methods. Using Arksey and O’Malley’s scoping review framework, six peer-reviewed, and four grey electronic literature databases in healthcare and the social sciences were searched in mid-2019. 111 full-text articles were retrieved, with 25 articles and reports meeting the inclusion criteria. Major themes were identified through thematic context analysis: (1) clinical, (2) system access to care, (3) research methodology, and (4) caregiving-related research gaps. Results. Findings include strategies for engaging stakeholder organizations and funding agencies, implications for other stakeholder groups such as clinicians and researchers, and highlight implications for policy (e.g., national framework discussion) and practice (e.g., healthcare provider education and training and public awareness). Conclusion. Reviewing and addressing targeted research gaps is essential to inform future directions in Canada and beyond.